Understanding the mechanisms through which an influential early childhood program boosted adult outcomes - James J. Heckman; Rodrigo Pinto; Peter Savelyev (Institute for the Study of Labor (IZA), 2012)
A growing literature establishes that high quality early childhood interventions targeted toward disadvantaged children have substantial impacts on later life outcomes. Little is known about the mechanisms producing these impacts. This paper uses longitudinal data on cognitive and personality traits from an experimental evaluation of the influential Perry Preschool program to analyze the channels through which the program boosted both male and female participant outcomes. Experimentally induced changes in personality traits explain a sizable portion of adult treatment effects.
Keywords: I21; I28; I29; J13; J15; J16; J24; O15; 330; cognitive traits; personality traits; externalizing behavior; academic motivation; factor analysis; human capital; human development; early childhood interventions; social experiments; Perry Preschool program; experimentally estimated production functions; Frühkindliche Bildung; Kinder; Wirkungsanalyse; Erwachsene; Kognition; Persönlichkeitspsychologie; Schätzung; USA